Good Corporate Governance Mechanism in Increasing Firm Value with Corporate Social Responsibility Disclosure and Green Intellectual Capital as Mediating Variables - Ryad, Ahmad Muhammad; Widyastuti, Tri; Darmansyah; Thaib, Danial (OGZ Research & Publishing, 2024)
Many factors influence Firm Value in a company, including good corporate governance, corporate social responsibility disclosure, green intellectual capital, economic, social and environmental. This research aims to analyze and evaluate empirically the influence of good corporate governance factors on Firm Value with corporate social responsibility and green intellectual capital as mediating variables. Research data was taken from telecommunications companies listed on the BEI (2017 -2022) based on the purposive sampling method. The research results prove that good corporate governance (GCG) has a positive effect on corporate social responsibility dislosure (CSRD), green intellectual capita (GIC), and firm value (FV). Corporate social responsibility dislosure and green intellectual capital indirectly mediate the influence of corporate governance on firm value, although the indirect influence is smaller than the direct influence of GCG on FV. This is because management cannot invest appropriately in developing the company's resources and social environment.